Stress analysis of short flat bar with projection using boundary element method - Nandar Aung, Wint Yee (2018)
Components with the projections on the bars, tubes, and plates are more commonly used nowadays to transmit the axial load. Due to the abrupt change in cross-sectional area, the local stress at that region becomes higher than the other regions and it leads to crack propagation. Therefore, fillets are introduced to reduce the stress concentration factor (SCF) at the high-stress point. Moreover, SCF and crack propagation can be affected by other geometric parameter ratios as well. Therefore, various case studies were conducted by using BEM to determine the effect on SCF and crack propagation in terms of overall stress intensity factor (SIF). Different cases were modeled by varying geometric parameter ratios under axial or shear loading with local or remote restraints. The first part of the study focused on the T-shaped model without the crack for stress concentration analysis. Furthermore, the second part focused on the model with the crack for crack propagation analysis. Through this investigation, the highest stress point was determined and subsequently, the effect on SCF and overall SIF was presented in graphs for different cases. From the results, it was concluded that R/d ratio has more prevailing effect on SCF than the other parameters and it is inversely proportional to SCF. Consequently, it was found that larger D/d could reduce the overall SIF whereas crack length is directly proportional to SIF. Therefore, this study allows for the optimization of the geometric parameters to reduce SCF and overall SIF.